2008
DOI: 10.2214/ajr.07.2816
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Reduced Radiation Dose of 16-MDCT for Detection of Nephrolithiasis and Ureterolithiasis

Abstract: An mA as low as 70 (35 mAs) is acceptable for evaluation of nephrolithiasis. However, the evaluation of ureterolithiasis is compromised with an mA of 70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…9,24,25 What is reasonable or acceptable in terms of diagnostic accuracy may change according to the clinical scenario, as well as the tolerance of the clinician and imaging specialist (and perhaps patient in a shared decision making model) for any uncertainty. 26,27 Although a reduced-dose CT may not be the most appropriate study in an elderly patient with a high potential for alternative causes of symptoms, it may be the best for determining need for intervention in young patients, many of whom receive repeated examinations with substantial radiation. 28 Gestalt pretest probability of kidney stone or an objective clinical prediction rule such as the Size Timing Onset Nausea Erthrocytes (STONE) score 19 may help select the most appropriate patients for substantial dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…9,24,25 What is reasonable or acceptable in terms of diagnostic accuracy may change according to the clinical scenario, as well as the tolerance of the clinician and imaging specialist (and perhaps patient in a shared decision making model) for any uncertainty. 26,27 Although a reduced-dose CT may not be the most appropriate study in an elderly patient with a high potential for alternative causes of symptoms, it may be the best for determining need for intervention in young patients, many of whom receive repeated examinations with substantial radiation. 28 Gestalt pretest probability of kidney stone or an objective clinical prediction rule such as the Size Timing Onset Nausea Erthrocytes (STONE) score 19 may help select the most appropriate patients for substantial dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The readers graded the overall image quality of the entire data set on a 4-point Likert scale 21 : score 4, very acceptable; score 3, acceptable; score 2, marginally to fairly acceptable; and score 1, not acceptable. In addition, the visibility of each stone was rated as follows 21 : score 4, clearly delineated; score 3, moderately visualized; score 2, marginally to fairly delineated; and score 1, not able to be depicted acceptably.…”
Section: Qualitative Image Evaluationmentioning
confidence: 99%
“…In addition, the visibility of each stone was rated as follows 21 : score 4, clearly delineated; score 3, moderately visualized; score 2, marginally to fairly delineated; and score 1, not able to be depicted acceptably.…”
Section: Qualitative Image Evaluationmentioning
confidence: 99%
“…Paulson and colleagues showed that by decreasing tube current in CT scans in a population of patients with renal and ureteral stones, the quality and detection were not significantly affected 16 . Although their group did not look at radiation dose reduction per say, tube current is directly proportional to exposure time; thus, they were able to show that reducing tube current offers adequate imaging while working to reduce radiation dose.…”
Section: Attempts Of Radiation Dose Reduction In Ctmentioning
confidence: 99%